Analisis Perbedaan Perkembangan Usaha Telur Asin di Sepanjang Jalan Pantai Utara Kabupaten Brebes Sebelum dan Sesudah Adanya Jalan Tol Pejagan-Semarang - Nurul Aeni Rahmahyanti; Achma Hendra Setiawan (Universitas Diponegoro, 2021)
The Pejagan-Semarang toll road development has a role in the development of the regional economy in improving the distribution of goods and services such as the salted egg business along the northern coast road of the Brebes Regency. The purpose of this research is to analyze the differences on the development of salted egg business along the north coast road of the Brebes Regency before and after the existence of the Pejagan-Semarang toll road which include sales volume, sales turnover, businiess profits, and the number of hours worked. This research used primary data with questionnaire data collection method. The questionnaire was collected from 101 respondents who were the business owners of salted eggs located along the northern coast road of Brebes Regency. The results showed that there were significant changes that can be seen at the level of significance which showed < 0,05 in sales volume, sales turnover, business profit, and the number of hours worked after the Pejagan-Semarang toll road.